(3QSGdI aj GdefWbs
(3ChdgG (B:s
(3ef GdeHOGA GdMce GdYdje GdajGV CYde Cf CQHGH GdejRGf bSehG GdbVjI Edi Medjg s
(3BNQgG (B:s
(3hGQaY Yfbc fGXQkG Edi GdCRgGQ Ef de jcf ai hgh fbdgG Yf NWg ESfGOg GdeDda s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI GdMLjGJ (B_ (3GdehUd (B(116) s
Keywords: (3GdeLGejYs